<span>Using the information we have
3x+4=40
Do the same to each side of the equation to eliminate for x.
3x+4=40 Minus 4 from each side
3x=40-4
3x=36
Divide 3 from each side
x=36/3
x=12
AC=3x+4
insert the value of x
3(12)+4=40
AC=40
AD=20</span>
Answer:A:0
Step-by-step explanation:hope this helps :)
Answer:
(5,6)
Step-by-step explanation:
-6x+6y=6
-6x + 3y =-12
Multiply the first equation by -1
6x-6y=-6
Add this to the second equation
6x-6y=-6
-6x + 3y =-12
---------------------
-3y = -18
Divide each side by -3
-3y/-3 = -18/-3
y =6
Now we need to find x
6x - 6y = -6
6x -6(6) = -6
6x -36 = -6
Add 36 to each side
6x-36+36 = -6+36
6x = 30
Divide each side by 6
6x/6 = 30/6
x =5
Answer:
2/7
Step-by-step explanation:
1
2
÷
1 3
4
=
1
2
÷
7
4
=
1
2
×
4
7
=
1 × 4
2 × 7
=
4
14
=
4 ÷ 2
14 ÷ 2
=
2
7